The Effect of Hydroxyapatite Nanocrystals on Osseointegration of Titanium Implants: An In Vivo Rabbit Study - Karin Breding; Ryo Jimbo; Mariko Hayashi; Ying Xue; Kamal Mustafa; Martin Andersson (International Journal of Dentistry)
Osseointegration is dependent on implant surface characteristics, including surface chemistry and topography. The presence of nanosized calcium phosphates on the implant surface is interesting to investigate since they affect both the nanotopography and surface chemistry, forming a bone mineral resembling surface. In this work, the osseointegration of titanium implants with and without the presence of hydroxyapatite (HA) nanocrystals has been evaluated in vivo. The integration was examined using removal torque measurements and real-time polymerase chain reaction (RT-PCR) analysis. The study was performed using two healing time points, 3 and 12 weeks. The results showed that the torque needed to remove the implants was insignificant between the non- and HA-coated implants, both at weeks 3 and 12. The RT-PCR, however, showed significant differences for osteoblast, osteoclast, and proinflammation markers when HA nanocrystals were present.